The ventromedial prefrontal cortex and emotion regulation: lost in translation?. (11th June 2022) - Alexander, Laith; Wood, Christian M.; Roberts, Angela C.
Abstract: Neuroimaging studies implicate the ventromedial prefrontal cortex (vmPFC) in a wide range of emotional and cognitive functions, and changes in activity within vmPFC have been linked to the aetiology and successful treatment of depression. However, this is a large, structurally heterogeneous region and the extent to which this structural heterogeneity reflects functional heterogeneity remains unclear. Causal studies in animals should help address this question but attempts to map findings from vmPFC studies in rodents onto human imaging studies highlight cross‐species discrepancies between structural homology and functional analogy. Bridging this gap, recent studies in marmosets – a species of new world monkey in which the overall organization of vmPFC is more like humans than that of rodents – have revealed that over‐activation of the caudal subcallosal region of vmPFC, area 25, but not neighbouring area 32, heightens reactivity to negatively valenced stimuli whilst blunting responsivity to positively valenced stimuli. These co‐occurring states resemble those seen in depressed patients, which are associated with increased activity in caudal subcallosal regions. In contrast, only reward blunting but not heightening of threat reactivity is seen following over‐activation of the structurally homologous region in rodents. To further advance understanding of the role of vmPFC in the aetiology and treatment of depression, future work should focus on the behaviourally specific networks by which vmPFC regions have their effects, together with characterization of cross‐species similarities and differences in function. Abstract : Abstract figure legend The value of non‐human primates in bridging the translational divide between correlative functional neuroimaging studies of the ventromedial prefrontal cortex (vmPFC) in humans and intervention studies of prelimbic (PL) and infralimbic (IL) cortex in rodents with a view to understanding the aetiology and treatment of mood and anxiety disorders.